Cobalt-containing aerogel supported ruthenium monatomic catalyst and preparation and application thereof
The preparation of ruthenium single-atom catalysts supported by cobalt-containing aerogels was solved by chemical precipitation and heat treatment, and the problems of high energy consumption and high cost of precious metal catalysts in the prior art were solved, thereby achieving efficient and low-cost ammonia production.
Patent Information
- Application Number
- CN202411766402.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art has problems such as high energy consumption, large carbon emissions and high cost of precious metal catalysts in the preparation of ammonia (NH3), which limits the efficient and low-cost production of ammonia.
The ruthenium single-atom catalyst supported by cobalt-containing aerogel is prepared by chemical precipitation and heat treatment, and the high surface area is used to achieve a highly efficient reaction of catalytic nitrate reduction to ammonia.
High-efficiency reduction of NO3- at low potentials was achieved, the Faraday efficiency of NH3 reached 96.3%, and the catalyst still maintained good performance after 6 cycles, significantly reducing the energy consumption and carbon emissions of ammonia production.
Smart Images

Figure HDA0005169057460000011 
Figure HDA0005169057460000021 
Figure HDA0005169057460000031
Abstract
Description
Technical Field
[0001] The invention belongs to the field of environmental protection and new energy technology, and particularly relates to a ruthenium single-atom catalyst supported by a cobalt-containing aerogel and a preparation and application thereof. Background Art
[0002] Ammonia (NH3) is an essential key chemical raw material for the production of fertilizers, pharmaceuticals, dyes and other high-value chemical products. At the same time, ammonia has high energy density and strong stability, and has unique advantages in energy storage and transportation. It is a promising carbon-free green energy. At present, the production of industrial NH3 mainly adopts the Haber process. However, this method has high energy consumption and large carbon dioxide emissions, causing serious damage to the global ecosystem. Electrochemical N2 reduction to NH3 driven by intermittent renewable energy has received widespread attention in recent years, but the extremely high dissociation energy of the N≡N bond (941kJ mol -1 ) and the low solubility of N2 in water greatly limit the Faradaic efficiency (FE) and yield of NH3. Nitrate not only has a lower NO bond energy (204 kJ mol -1 ), and has good water solubility, so the electrochemical nitrate reduction reaction (NO3RR) provides a feasible strategy for the production of ammonia (NH3). In fact, nitrate is a major pollutant in various water bodies, mostly from industrial wastewater, fertilizers and livestock manure. The electrochemical nitrate reduction reaction to produce ammonia is an important electrochemical reaction aimed at reducing nitrate (NO3 - ) is reduced to ammonia. Therefore, NO3RR represents a green and sustainable strategy that can achieve the goal of “killing two birds with one stone”.
[0003] Precious metal catalysts usually have higher catalytic activity and reaction selectivity, and can effectively catalyze reactions at lower temperatures. However, the reserves of precious metals in nature are limited and expensive, which makes the production cost of precious metal catalysts high, thus limiting their large-scale application. In order to prepare low-cost, efficient and stable catalysts, alloying a small amount of precious metals with non-precious metals is currently an important way to reduce costs and improve catalytic performance. Summary of the invention
[0004] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a ruthenium single-atom catalyst supported by a cobalt-containing aerogel.
[0005] The present invention prepares a cobalt-containing aerogel-supported ruthenium single-atom catalyst by a simple and easy-to-operate chemical precipitation method and a heat treatment method. The preparation method has the advantages of simple operation and process safety, and shows good potential for industrial application.
[0006] Another object of the present invention is to provide a ruthenium single-atom catalyst supported on a cobalt-containing aerogel prepared by the above method.
[0007] The noble metal ruthenium in the catalyst obtained by the present invention exists in the form of single atoms, and the ruthenium metal content is low. The cobalt-containing aerogel has a special sheet structure. The special structure of the single atom and the large surface area of the aerogel allow the material to expose a large number of catalytic active sites.
[0008] Another object of the present invention is to provide an application of the above-mentioned cobalt-containing aerogel-supported ruthenium single-atom catalyst in catalyzing nitrate reduction to produce ammonia.
[0009] The catalyst of the present invention has a large number of active sites on its surface and exhibits excellent catalytic activity and stability in the electrocatalytic nitrate reduction reaction.
[0010] The purpose of the present invention is achieved through the following solutions:
[0011] A method for preparing a cobalt-containing aerogel-supported ruthenium single-atom catalyst comprises the following steps:
[0012] (1) Preparation of cobalt-containing aerogel: polyaniline is carbonized under an inert gas, cooled to room temperature, cobalt salt and water are added to the carbonized product, mixed, a reducing agent solution is added, and the product is allowed to stand for aging to obtain cobalt-containing aerogel;
[0013] (2) Preparation of ruthenium single atom catalyst: ruthenium salt solution, zirconium chloride, 2-aminoterephthalic acid and organic solvent are uniformly mixed, glacial acetic acid is added, and heated for reaction; then calcined under an inert atmosphere, and then immersed in a hydrofluoric acid solution to remove zirconic acid, thereby obtaining a ruthenium single atom catalyst;
[0014] (3) Grinding the cobalt-containing aerogel obtained in step (1) and the ruthenium single-atom catalyst obtained in step (2) uniformly, and heating them in an air atmosphere to obtain a ruthenium single-atom catalyst supported on the cobalt-containing aerogel.
[0015] The inert gas in step (1) is nitrogen.
[0016] The cobalt salt in step (1) is cobalt chloride.
[0017] The reducing agent of the reducing agent solution in step (1) is sodium borohydride; the solvent is water; and the concentration of the reducing agent in the reducing agent solution is 0.26 mol / L.
[0018] The carbonization temperature in step (1) is 850°C, the time is 4h, and the heating rate is 5°C / min.
[0019] The usage ratio of the carbonization product, cobalt salt and water in step (1) is 20 mg: 0.8 mmol: 30 mL.
[0020] The molar ratio of the cobalt salt to the reducing agent in step (1) is 0.8:2.6.
[0021] The temperature of the static aging in step (1) is room temperature and the time is 24 hours.
[0022] After the static aging in step (1), the product is washed alternately with water and ethanol, and then freeze-dried to obtain a cobalt-containing aerogel.
[0023] The solute of the ruthenium salt solution in step (2) is ruthenium chloride, and the solvent is dimethylformamide; the concentration of the ruthenium salt solution is 0.0048 mol / L.
[0024] The organic solvent in step (2) is dimethylformamide.
[0025] In step (2), the dosage ratio of the ruthenium salt solution, zirconium chloride, 2-aminoterephthalic acid and organic solvent is 27 μL: 0.04 mmol: 0.04 mmol: 10 mL.
[0026] The usage ratio of glacial acetic acid to zirconium chloride in step (2) is 1.2 mL:0.04 mmol.
[0027] After adding glacial acetic acid in step (2), the mixed solution was ultrasonicated for 30 minutes.
[0028] The temperature of the heating reaction in step (2) is 120° C. and the time is 24 hours.
[0029] After the heating reaction in step (2), the mixture is cooled to room temperature, and the obtained product is washed alternately with methanol and dimethylformamide and dried in vacuo.
[0030] The inert atmosphere in step (2) is argon.
[0031] The calcination temperature in step (2) is 700°C, the calcination time is 3h, and the heating rate is 5°C / min.
[0032] The ratio of hydrofluoric acid to water in the hydrofluoric acid solution of step (2) is 0.1 mol:15 mL.
[0033] The soaking time in step (2) is 2 hours.
[0034] After the soaking in step (2), the product is centrifuged, and the obtained solid is washed alternately with methanol and water and dried in vacuum to obtain a ruthenium single atom catalyst.
[0035] The mass ratio of the cobalt-containing aerogel to the ruthenium single-atom catalyst in step (3) is 10:1.
[0036] The temperature of the heating treatment in step (3) is 200°C, the time is 2h, and the heating rate is 5°C / min.
[0037] After the heating treatment in step (3), the product is cooled to room temperature.
[0038] A ruthenium single atom catalyst supported by a cobalt-containing aerogel prepared by the method.
[0039] The above-mentioned cobalt-containing aerogel-supported ruthenium single-atom catalyst is used in catalyzing nitrate reduction to produce ammonia.
[0040] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0041] (1) The preparation method is simple and easy: the present invention adopts chemical precipitation method and heat treatment method, and the reaction process is simple and easy to operate and control, so it is easy to scale up for mass production.
[0042] (2) Contains a large number of catalytic active sites: The catalyst synthesized in the present invention has a special structure. The multilayer structure and single-atom characteristics of the aerogel make its surface contain a large number of catalytic active sites.
[0043] (3) The catalyst preparation process is safe: The catalyst preparation process of this method is carried out at room temperature and pressure, which is safe and reliable.
[0044] (4) Excellent performance: The best catalyst prepared has a -0.5 V potential for NO3 - The reduction to NH3 has excellent performance, with a Faradaic efficiency of NH3 of up to 96.3%, and only a slight attenuation of the Faradaic efficiency and yield of NH3 after 6 catalytic cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 These are transmission electron microscope (TEM) photos of the ruthenium single-atom catalyst supported by the cobalt-containing aerogel obtained in Example 1 at different magnifications.
[0046] Figure 2 The transmission electron microscope image of the cobalt-containing aerogel-supported ruthenium single atom catalyst obtained in Example 1 at a scale of 10 nm, the element mapping distribution map of the ruthenium single atom, and the EDS element content map.
[0047] Figure 3 This is the X-ray photoelectron spectrum of the ruthenium single-atom catalyst supported by the cobalt-containing aerogel obtained in Example 1.
[0048] Figure 4 The ruthenium single-atom catalyst supported by the cobalt-containing aerogel obtained in Example 1 was heated to 0.5 mol L -1 1 mol L -1Characterization of the performance of catalytic nitrate reduction to ammonia in NaOH solution; wherein, a is the Faraday efficiency and yield of NH3 of the products obtained in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 4 at -0.5V; b is the Faraday efficiency and yield of NH3 of the product obtained in Example 1 at different potentials; c is the half-cell energy diagram at different potentials; d is the stability characterization of the catalyst obtained in Example 1.
[0049] Figure 5 The ruthenium single atom supported by the cobalt-containing aerogel obtained in Example 1 was used as a catalyst, and Na 14 NO3 and Na 15 Nitrate reduction products with NO3 as N source 1 H-NMR spectrum.
[0050] Figure 6 This is a transmission electron microscope (TEM) photograph of the product obtained in Comparative Example 4.
[0051] Figure 7 This is a spherical aberration electron microscope image of the ruthenium single atom catalyst supported by the cobalt-containing aerogel obtained in Example 1. The circled part in the image is the ruthenium single atom site. DETAILED DESCRIPTION
[0052] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0053] Unless otherwise specified, the reagents used in the examples can be purchased from the market.
[0054] Example 1
[0055] (1) Weigh 10 g of polyaniline at room temperature and place it in a porcelain boat of appropriate size without covering it;
[0056] (2) Place the obtained powder in a tube furnace, introduce nitrogen as a protective gas, and control the gas flow rate to one bubble per second. Heat from room temperature to 850 degrees Celsius at a rate of 5 degrees Celsius per minute, and continue heating for four hours to carbonize the material;
[0057] (3) The product obtained in step (2) was naturally cooled to room temperature, 20 mg was weighed, and 120 mg of cobalt chloride hexahydrate was weighed, and both were dissolved in 30 mL of deionized water;
[0058] (4) 100 mg of sodium borohydride was dissolved in 10 mL of deionized water, and the sodium borohydride aqueous solution was poured into the solution obtained in (3), and allowed to stand and age at room temperature for 24 hours. The product was washed alternately with deionized water and ethanol and then freeze-dried to obtain a cobalt-containing aerogel;
[0059] (5) Weigh 10 mg of ruthenium chloride powder and dissolve it in 10 mL of dimethylformamide solution to prepare a 1 mg / mL solution;
[0060] (6) Take 27 μL of the ruthenium chloride solution obtained in (5), weigh 10.49 mg of zirconium chloride and 8.15 mg of 2-aminoterephthalic acid, and dissolve them together in 10 mL of dimethylformamide solution;
[0061] (7) Add 1.2 mL of glacial acetic acid to the solution obtained in (6), sonicate for 30 minutes using an ultrasonic machine, then transfer to an oven and heat at 120 degrees Celsius for 24 hours. After heating, cool naturally to room temperature, and wash the product alternately with methanol and dimethylformamide and dry in vacuo;
[0062] (8) Place the product obtained in (7) in a porcelain boat and place it in a tube furnace. Add argon as a protective gas and control the gas flow rate to one bubble per second. Raise the temperature at a rate of 5 degrees Celsius per minute from room temperature to 700 degrees Celsius and maintain for 3 hours.
[0063] (9) The black powder obtained by calcining (8) was soaked in 15 mL of deionized water containing 0.1 mol of hydrofluoric acid for 2 hours, and the concentration of hydrofluoric acid was 40% w / w. In this step, the zirconic acid in the crude product was washed clean, and the product was centrifuged and washed alternately with methanol and water, and vacuum dried to obtain a ruthenium single atom catalyst;
[0064] (10) Weigh 10 mg of the product obtained in (4) and 1 mg of the product obtained in (9), grind and mix them evenly, place them in a porcelain boat and send them into a tube furnace. In an air atmosphere, heat them at a rate of 5 degrees Celsius per minute from room temperature to 200 degrees Celsius and keep them for 2 hours. After heating, naturally cool them to room temperature to obtain the final product, a cobalt-containing aerogel-supported ruthenium single atom catalyst.
[0065] Performance structure analysis
[0066] Figure 1 The transmission electron microscope (TEM) photos of the ruthenium single atom catalyst supported on the cobalt-containing aerogel of Example 1 at different magnifications can be clearly seen from the TEM image that the synthesized cobalt-containing aerogel has a nanosheet structure. The nanosheets are stacked layer by layer to form a multi-layer special structure with pores, which can expose a large number of active sites and provide more attachment points for single atoms.
[0067] Figure 2The transmission electron microscope image of the ruthenium single atom catalyst supported by the cobalt-containing aerogel obtained in Example 1 at a scale of 10 nm, the element mapping distribution map of the ruthenium single atom at 10 nm, and the EDS element content map.
[0068] Figure 3 This is the X-ray photoelectron (XPS) spectrum of the ruthenium single-atom catalyst supported on the cobalt-containing aerogel of Example 1. The characterization shows that both Co and Ru elements exist in the product, proving the successful synthesis of the product.
[0069] Figure 4 b is the ruthenium single atom catalyst supported by the cobalt-containing aerogel in Example 1 at a NaNO3 concentration of 0.1 mol L -1 1 mol L -1 Electrocatalysis of NO3 at different potentials in NaOH solution - The Faraday efficiency and yield of reduced NH3 are shown in the figure. The amount of catalyst used in the test is 5 mg / mL. It can be seen from the figure that at a low potential of -0.5 V, the Faraday efficiency of NH3 reaches a maximum value of 96.3%, and the yield can reach 1.5 mmol h -1 mg -1 . Figure 4 Figure c is a half-cell energy diagram at different potentials, indicating that the catalyst has excellent energy conversion efficiency; Figure 4 Figure d shows that after 6 cycles of catalytic experiments, the ruthenium single-atom catalyst supported by cobalt aerogel still has good catalytic activity, and the Faraday efficiency of NH3 is 90.2%, indicating that this catalyst has good stability.
[0070] Figure 5 The ruthenium single atom catalyst supported by the cobalt-containing aerogel of Example 1 was used as the catalyst, and Na 14 NO3 and Na 15 Nitrate reduction products with NO3 as nitrogen source 1 H-NMR spectrum, 15 NH3 has only two peaks in the NMR spectrum, 14 NH3 will have three peaks at the corresponding chemical shift. As can be seen from the figure, when Na 15 When NO3 is the nitrogen source, all the products are 15 NH3, which means that all the NH3 in the system after reduction comes from the added NO3 - Rather than other nitrogen sources in the environment.
[0071] Comparative Example 1
[0072] (1) Weigh 10 g of polyaniline at room temperature and place it in a porcelain boat of appropriate size without covering it;
[0073] (2) Place the obtained powder in a tube furnace, introduce nitrogen as a protective gas, and control the gas flow rate to one bubble per second. Heat from room temperature to 850 degrees Celsius at a rate of 5 degrees Celsius per minute, and continue heating for four hours to carbonize the material;
[0074] (3) The product obtained in step (2) was naturally cooled to room temperature, 20 mg was weighed, and 120 mg of cobalt chloride hexahydrate was weighed, and both were dissolved in 30 mL of deionized water;
[0075] (4) 100 mg of sodium borohydride was dissolved in 10 mL of deionized water, and the sodium borohydride aqueous solution was poured into the solution obtained in (3), and allowed to stand and age at room temperature for 24 hours. The product was washed alternately with deionized water and ethanol and then freeze-dried to obtain a cobalt-containing aerogel;
[0076] Comparative Example 2
[0077] (1) Weigh 10 mg of ruthenium chloride powder and dissolve it in 10 mL of dimethylformamide solution to prepare a 1 mg / mL solution;
[0078] (2) Take 27 μL of the ruthenium chloride solution obtained in (1), weigh 10.49 mg of zirconium chloride and 8.15 mg of 2-aminoterephthalic acid, and dissolve them together in 10 mL of dimethylformamide solution;
[0079] (3) Add 1.2 mL of glacial acetic acid to the solution obtained in (2), sonicate for 30 minutes using an ultrasonic machine, then transfer to an oven and heat at 120 degrees Celsius for 24 hours. After heating, cool naturally to room temperature, and wash the product alternately with methanol and dimethylformamide, and dry in vacuo;
[0080] (4) Place the product obtained in (3) in a porcelain boat and place it in a tube furnace. Add argon as a protective gas and control the gas flow rate to one bubble per second. Raise the temperature at a rate of 5 degrees Celsius per minute from room temperature to 700 degrees Celsius and maintain for 3 hours.
[0081] (5) The black powder obtained by calcining (4) was soaked in 15 mL of deionized water containing 0.1 mol of hydrofluoric acid for 2 hours, and the concentration of hydrofluoric acid was 40% w / w. The product was centrifuged, washed alternately with methanol and water, and dried in vacuum to obtain a ruthenium single atom catalyst.
[0082] Comparative Example 3
[0083] (1) Weigh 10 mg of ruthenium chloride powder and dissolve it in 10 mL of dimethylformamide solution to prepare a 1 mg / mL solution;
[0084] (2) Take 27 μL of the ruthenium chloride solution obtained in (1), weigh 10.49 mg of zirconium chloride and 7.49 mg of terephthalic acid, and dissolve them together in 10 mL of dimethylformamide solution;
[0085] (3) Add 1.2 mL of glacial acetic acid to the solution obtained in (2), sonicate for 30 minutes using an ultrasonic machine, then transfer to an oven and heat at 120 degrees Celsius for 24 hours. After heating, cool naturally to room temperature, and wash the product alternately with methanol and dimethylformamide, and dry in vacuo;
[0086] (4) Place the product obtained in (3) in a porcelain boat and place it in a tube furnace. Add argon as a protective gas and control the gas flow rate to one bubble per second. Raise the temperature at a rate of 5 degrees Celsius per minute from room temperature to 700 degrees Celsius and maintain for 3 hours.
[0087] (5) The black powder obtained by calcining (4) was soaked in 15 mL of deionized water containing 0.1 mol of hydrofluoric acid for 2 hours, and the concentration of hydrofluoric acid was 40% w / w. The product was centrifuged, washed alternately with methanol and water, and vacuum dried to obtain ruthenium particles.
[0088] Comparative Example 4
[0089] Comparative Example 4 is substantially the same as Example 1, except that in step (6), 8.15 mg of 2-aminoterephthalic acid is replaced by 7.49 mg of terephthalic acid.
[0090] Figure 6 This is a SEM image of the product of Comparative Example 4. It can be seen from the figure that it is in an agglomerated state, and the particle size is no longer a single-atom material. After the reaction is completed, the ruthenium nanomaterials obtained are all agglomerated and cannot form single atoms. The reason is: the type of ligand changes, and the ligand cannot form a bond with ruthenium in time during the reaction, which ultimately leads to the synthesis of ruthenium particles instead of ruthenium single atoms, or causes a large amount of ruthenium to agglomerate into clusters and enrich on the surface, and ultimately cannot form uniformly dispersed ruthenium single atoms.
[0091] Figure 4 The products obtained from the left to right in a are Comparative Example 1, Example 1, Comparative Example 4 and Comparative Example 2 at a NaNO3 concentration of 0.5 mol L -1 1 mol L -1 Electrocatalysis of NO3 in NaOH solution at -0.5V - From the Faraday efficiency and yield of reduced NH3, it can be seen that at a potential of -0.5 V, the Faraday efficiency corresponding to the products obtained in Examples 1, 2, and 4 is no more than 90% at most, which is lower than the performance of the catalyst obtained in Example 1.
[0092] Example 1 has the best catalytic performance, and its structure and performance are the most representative. In terms of structure, ruthenium atoms are evenly dispersed on the cobalt-containing aerogel without agglomeration into clusters. The more active sites are exposed, the better the performance will be. By electrocatalyzing NO3 at different potentials, - After analyzing the reduction products, we found that at a potential of -0.5 V, it electrocatalyzed NO3 - The reduction has the best performance. At this potential, the Faradaic efficiency of NH3 reaches 96.3% and the yield can reach 1.5 mmol h -1 mg -1 At the same time, after 6 cycles of catalytic experiments at this potential, the Faraday efficiency and yield of NH3 only slightly decayed, indicating that the stability of ruthenium single atoms is very good, and it can be used as a catalyst to catalyze NO3 in industrial wastewater. - Reduction to NH3 has great application prospects and industrial value.
[0093] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a ruthenium single-atom catalyst supported by a cobalt-containing aerogel, characterized in that: The following steps are involved: (1) Preparation of cobalt-containing aerogel: polyaniline is carbonized under an inert gas, cooled to room temperature, cobalt salt and water are added to the carbonized product, mixed, a reducing agent solution is added, and the product is allowed to stand for aging to obtain cobalt-containing aerogel; (2) Preparation of ruthenium single atom catalyst: ruthenium salt solution, zirconium chloride, 2-aminoterephthalic acid and organic solvent are uniformly mixed, glacial acetic acid is added, and heated for reaction; then calcined under an inert atmosphere, and then immersed in a hydrofluoric acid solution to remove zirconic acid, thereby obtaining a ruthenium single atom catalyst; (3) Grinding the cobalt-containing aerogel obtained in step (1) and the ruthenium single-atom catalyst obtained in step (2) uniformly, and heating them in an air atmosphere to obtain a ruthenium single-atom catalyst supported on the cobalt-containing aerogel.
2. The method for preparing the cobalt-containing aerogel-supported ruthenium single-atom catalyst according to claim 1, characterized in that: The inert gas in step (1) is nitrogen; The cobalt salt in step (1) is cobalt chloride; The reducing agent of the reducing agent solution in step (1) is sodium borohydride; the solvent is water; the concentration of the reducing agent in the reducing agent solution is 0.26 mol / L; The carbonization temperature in step (1) is 850°C, the time is 4h, and the heating rate is 5°C / min.
3. The method for preparing the cobalt-containing aerogel-supported ruthenium single-atom catalyst according to claim 1, characterized in that: In step (1), the carbonization product, cobalt salt and water are used in a ratio of 20 mg: 0.8 mmol: 30 mL; The molar ratio of the cobalt salt to the reducing agent in step (1) is 0.8:2.6; The temperature of the static aging in step (1) is room temperature and the time is 24 hours.
4. The method for preparing the cobalt-containing aerogel-supported ruthenium single-atom catalyst according to claim 1, characterized in that: The solute of the ruthenium salt solution in step (2) is ruthenium chloride, and the solvent is dimethylformamide; the concentration of the ruthenium salt solution is 0.0048 mol / L; The organic solvent in step (2) is dimethylformamide.
5. The method for preparing the cobalt-containing aerogel-supported ruthenium single-atom catalyst according to claim 1, characterized in that: In step (2), the ratio of the ruthenium salt solution, zirconium chloride, 2-aminoterephthalic acid and organic solvent is 27 μL: 0.04 mmol: 0.04 mmol: 10 mL; The ratio of glacial acetic acid to zirconium chloride in step (2) is 1.2 mL:0.04 mmol; The temperature of the heating reaction in step (2) is 120° C. and the time is 24 hours.
6. The method for preparing the cobalt-containing aerogel-supported ruthenium single-atom catalyst according to claim 1, characterized in that: The inert atmosphere in step (2) is argon; The calcination temperature in step (2) is 700°C, the calcination time is 3h, and the heating rate is 5°C / min.
7. The method for preparing the cobalt-containing aerogel-supported ruthenium single-atom catalyst according to claim 1, characterized in that: The ratio of hydrofluoric acid to water in the hydrofluoric acid solution of step (2) is 0.1 mol:15 mL; The soaking time in step (2) is 2 hours.
8. The method for preparing the cobalt-containing aerogel-supported ruthenium single-atom catalyst according to claim 1, characterized in that: The mass ratio of the cobalt-containing aerogel to the ruthenium single-atom catalyst in step (3) is 10:1; The temperature of the heating treatment in step (3) is 200°C, the time is 2h, and the heating rate is 5°C / min.
9. A ruthenium single atom catalyst supported on a cobalt-containing aerogel prepared by the method according to any one of claims 1 to 8.
10. Use of the ruthenium single-atom catalyst supported by the cobalt-containing aerogel according to claim 9 in catalyzing nitrate reduction to produce ammonia.
Citation Information
Cited By
Iron-manganese diatomic catalyst modified by iron cluster as well as preparation method and application of iron-manganese diatomic catalyst
CN120119287A